Outcomes after Anatomic Double-Bundle Posterior Cruciate Ligament Reconstructions Using Transtibial and Tibial Inlay Techniques - Temperato, Joseph; Rucinski, Kylee; Cook, James L.; Meers, Aaron; Albuquerque, João Bourbon de, II; Stannard, James P. (The Journal of Knee Surgery, 2023)
Surgical reconstruction is recommended for symptomatic posterior cruciate ligament (PCL) deficiency. While anatomic double-bundle PCL reconstruction (PCLR) has been reported to be associated with biomechanical and clinical advantages over other methods, there is still debate regarding the optimal technique for tibial positioning and fixation. Based on reported advantages and disadvantages, we employed two tibial fixation techniques, transtibial (TT) and tibial inlay (TI) for anatomic double-bundle PCLR with technique selection based on body mass index, comorbidities, and primary versus revision surgery. This study aimed to compare clinical outcomes following PCLR utilizing either TT or TI techniques to validate relative advantages, disadvantages, and indications for each based on the review of prospectively collected registry data. For 37 patients meeting inclusion criteria, 26 underwent arthroscopic TT PCLR using all-soft- tissue allograft with suspensory fixation in the tibia and 11 patients underwent open TI PCLR using an allograft with calcaneal bone block and screw fixation in the tibia. There were no significant preoperative differences between cohorts. Success rates were 96% for TT and 91% for TI with all successful cases documented to be associated with good-to-excellent posterior stability and range of motion in the knee at the final follow-up. In addition, patient-reported outcome scores were within clinically meaningful ranges for pain, function, and mental health after PCLR in both cohorts, suggesting similarly favorable functional, social, and psychological outcomes. Patient-reported pain scores at 6 months postoperatively were significantly (p = 0.042) lower in the TT cohort, which was the only statistically significant difference in outcomes noted. The results of this study support the use of TT and TI techniques for double-bundle anatomic PCLR in restoring knee stability and patient function when used for the treatment of isolated and multiligamentous PCL injuries. The choice between tibial fixation methods for PCLR can be appropriately based on patient and injury characteristics that optimize respective advantages for each technique.
Keywords: posterior cruciate ligament; reconstruction; transtibial inlay; tibial inlay